The influence of English on the languages in the Nordic countries - Aijmer, Karin; Melchers, Gunnel (Nordic Journal of English Studies, 2004)
English has a special position in the world as a global or international language. This global English is sometimes described as a "lingua franca"; it is used by a large number of speakers in Europe and internationally. It functions as a life-line for the tourist and as a language for communication in the sciences, transport and business world and is important for cultural exchange.